Health provider perspectives on the implementation of the same-day-ART initiation policy in the Gauteng province of South Africa - Dorina Onoya; Idah Mokhele; Tembeka Sineke; Bulelwa Mngoma; Aneesa Moolla; Marnie Vujovic; Jacob Bor; Jonas Langa; Matthew P. Fox (BMC, 2021)
Abstract Background In September 2016, South Africa (SA) began implementing the universal-test-and-treat (UTT) policy in hopes of attaining the UNAIDS 90-90-90 targets by 2020. The SA National Department of Health provided a further directive to initiate antiretroviral therapy (ART) on the day of HIV diagnosis in September 2017. We conducted a qualitative study to determine the progress in implementing UTT and examine health providers' perspectives on the implementation of the same-day initiation (SDI) policy, six months after the policy change. Methods We conducted in-depth interviews with three professional nurses, and four HIV lay counsellors of five primary health clinics in the Gauteng province, between October and December 2017. In September 2018, we also conducted a focus group discussion with ten professional nurses/clinic managers from ten clinic facilities. The interviews and focus groups covered the adoption and implementation of UTT and SDI policies. Interviews were conducted in English, Sotho or Zulu and audio-recorded with participant consent. Audio-recordings were transcribed verbatim, translated to English and analysed thematically using NVivo 11. Results The data indicates inconsistencies across facilities and incongruities between counsellor and nursing provider perspectives regarding the SDI policy implementation. While nurses highlighted the clinical benefits of early ART initiation, they expressed concerns that immediate ART may be overwhelming for some patients, who may be unprepared and likely to disengage from care soon after the initial acceptance of ART. Accordingly, the SDI implementation was slow due to limited patient demand, provider ambivalence to the policy implementations, as well as challenges with infrastructure and human resources. The process for assessing patient readiness was poorly defined by health providers across facilities, inconsistent and counsellor dependent. Providers were also unclear on how to ensure that patients who defer treatment return for ongoing counselling. Conclusions Our results highlight important gaps in the drive to achieve the ART initiation target and demonstrate the need for further engagement with health care providers around the implementation of same-day ART initiation, particularly with regards to infrastructural/capacity needs and the management of patient readiness for lifelong ART on the day of HIV diagnosis. Additionally, there is a need for improved promotion of the SDI provision both in health care settings and in media communications to increase patient demand for early and lifelong ART.